A segmental analysis of the Japanese negation verb variation: A phonological perspective - Delfariyadi, Fahri; Sunarni, Nani; Ardiati, Riza Lupi (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2022)
Within the field of Japanese linguistics, the topics on segmental analysis of verb variation have rarely been studied from the phonological perspective. On the other hand, verb modifications have been frequently observed to occur in oral communication. This study addresses a segmental analysis within the variation of Japanese negation verb from the phonological standpoint. It employed a qualitative descriptive approach with the data gathered from the Japanese animated series Orange (Hamasaki & Nakayama, 2016). Excerpts of the data were in the form of conversation fragments, which were analyzed using the articulatory phonetic identity technique. The analysis resulted in five found variations: -nai, -nnai, -nee, -nnee, and -ai deletion. The presence of sounds in the phonological environment caused phonological variation, which affected the internal structure of the verb. As a result, the phonological rules are applied to showcase the phonological process in the verb. It was also found that segmental processing does not necessarily reduce the amount of mora in verbs. Segmental processes, on the other hand, can change the mora structure without reducing the mora. Additionally, the current study shows vowel coalescence associated with the male speech in Japanese.